Membrane Transport Proteins Expressed in the Renal Tubular Epithelial Cells of Seawater and Freshwater Teleost Fishes - Kato, Akira; Nagashima, Ayumi; Hosono, Kohei; Romero, Michael F. (Frontiers in Physiology, 2022)
The kidney is an important organ that maintains body fluid homeostasis in seawater and freshwater teleost fishes. Seawater teleosts excrete sulfate and magnesium in small amounts of isotonic urine, and freshwater teleosts excrete water in large amounts of hypo-osmotic urine. The volume, osmolality, and ionic compositions of the urine are regulated mainly by membrane transport proteins expressed in the renal tubular epithelial cells. Gene expression, immunohistochemical, and functional analyses of the fish kidney identified membrane transport proteins involved in the secretion of sulfate and magnesium ions by the proximal tubules and reduction of urine volume by the collecting ducts in seawater teleosts, and excretion of water as hypotonic urine by the distal tubules and collecting ducts in freshwater teleosts. These studies promote an understanding of how the kidney contributes to the seawater and freshwater acclimation of teleosts at the molecular level.